PENGARUH SUBSTITUSI AGREGAT HALUS SABANG TERHADAP KINERJA LASTON LAPIS AUS (AC-WC) - Mohd Fahmi Abdya P.; Sofyan M. Saleh; Yusria Darma (Prodi Magister Teknik Sipil Unsyiah, 2018)
Asphalt and Aggregate is the main ingredient of the asphalt concrete layer which determines the quality of asphalt pavement. One of the main cause of the damage and decrease of asphalt pavement strength on the road is the low strength and durability of the asphalt mixture. . But in the other side the utilization of local materials is expected to be used maximally to improve efficiency in terms of financing, especially for island area such as Sabang city of Aceh Province. Importing material from Ace Besar district is need a big cost. In solving this problem therefore it is necessary to maximize the use of local material. this research is done for find out the effect of the use of fine aggregate on the characteristics of the coarse layer of asphalt concrete mixture characteristics (AC-WC)with the addition of Sabang fine aggregate starting from 0%, 25%, 50%, 75% and 100%. The initial step in this research is find the value of optimum asphalt content (KAO).The result of this research shows that the more composition of the Sabang fine aggregate then the decreasing the stability value. The highest stability value is on the asphalt concrete mixture without Sabang fine aggregate substitution with the asphalt content is 5,38% with the amount of 1.658,73 kg and the lowest stability value is on the asphalt concrete mixture with 100% of Sabang fine aggregate substitution with asphalt content is 6,35% in the amount of 979,35 kg. The maximum composition of sabang fine aggregate which pass the requirement specification of Asphalt concrete AC-WC volumetric characteristic is 50% on the level of 5,87% with the stability value is 1.225,81 kg.